Analysis of welding residual stress formation behavior during circumferential TIG welding of a pipe. (November 2018) - Wu, Chunbiao; Kim, Jae-Woong
Abstract: The objective of this study is to analyze the formation behavior of welding residual stresses during the circumferential TIG butt welding of pipes. A three-dimensional thermo-elastic-plastic numerical model has been developed by using MSC-Marc software to predict welding residual stress distributions during single-pass welding of pipes. Using a numerical computational approach, the mechanisms of the changes in stress and strain throughout the pipe welding process is described. Compared with the features of butt welded plate joints, the distribution of welding residual stress in butt welded pipe structures is obviously different. Considering the deformation effect on the plastic strain distribution, the calculation results indicate that the axial and hoop compressive plastic strain at the inner surface of welded pipes is much larger than that at the outer surface. As a result, the tensile axial and hoop residual stress is generated at the inner surface due to the thermal contracting deformation. Consequently, compressive axial residual stress occurs at the outer surface because of the inward contracting deformation and internal stress self-balance. Moreover, it is investigated and explained the phenomenon in which both axial and hoop residual stresses have sharp gradients near the weld stop location at the overlapped weld line of pipe. Because of redistribution of axial residual stresses and hoop plastic flow behaviors, residual stresses near the weld stop location could be changed. Highlights: Welding residual stress distributions of pipe joints are different from those of plate joints. 3D numerical model simulates the residual stress formation behavior of a pipe welding. In pipe welding an unique residual stress are occurred near the weld stop location. Sharp gradients of stress at the weld stop are induced by the plastic flow during cooling.